2016
DOI: 10.1371/journal.pone.0153958
|View full text |Cite
|
Sign up to set email alerts
|

Improving Sprint Performance in Soccer: Effectiveness of Jump Squat and Olympic Push Press Exercises

Abstract: Training at the optimum power load (OPL) is an effective way to improve neuromuscular abilities of highly trained athletes. The purpose of this study was to test the effects of training using the jump squat (JS) or Olympic push-press (OPP) exercises at the OPL during a short-term preseason on speed-power related abilities in high-level under-20 soccer players. The players were divided into two training groups: JS group (JSG) and OPP group (OPPG). Both groups undertook 12 power-oriented sessions, using solely J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
78
1
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 50 publications
11
78
1
8
Order By: Relevance
“…Changes in the level of power during the preparatory period among the Radom players were negligible, and similar observations were noted during the preparation period in Brazilian players [39]. The results of both studies may indicate that there is little chance of developing muscle power in the preparation of a football team for league competitions.…”
Section: Powersupporting
confidence: 74%
“…Changes in the level of power during the preparatory period among the Radom players were negligible, and similar observations were noted during the preparation period in Brazilian players [39]. The results of both studies may indicate that there is little chance of developing muscle power in the preparation of a football team for league competitions.…”
Section: Powersupporting
confidence: 74%
“…In this regard, several studies have confirmed the chronic effectiveness of JS on improving sports performance [23,35,36]. Remarkably, it seems that these positive effects are independent of the “JS loading condition/variation”, although this parameter may provoke specific/distinct adaptations in the force-velocity curve.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, JS is suggested to better discriminate between players with higher and lower sprint, and COD and jumping abilities than HS, and possibly training using JS would be more effective than training using HS for improving performance in rugby sevens players. Because of the well-established strong relationship between JS MPP and specific performance in different sports [16,17,19,45,46] and the effectiveness of JS training in improving jumping and sprinting capacities [13,23,35,36], this exercise has been incorporated in assessments and training routines by elite athletes. To our knowledge, this is the first study to show that JS relates more closely to functional task performances than HS using the median split technique.…”
Section: Discussionmentioning
confidence: 99%
“…Jump-squat has been shown to improve jump height (17,25,38), as well as sprint performance (15,16,38). However, since the increased role of change of direction (COD) in soccer (8), the effects of jump-squat training on COD were only recently investigated, reporting improvements in COD after jump-squat training only (26,27), or jump-squat added to a traditional strength training program (23). Importantly, jump-squat training was shown to improve physical ability in soccer players in pre-season (27) and to counteract the decrease in speed and power performance due to the high endurance training load the players undergo before the season begins (28).…”
Section: Introductionmentioning
confidence: 99%